2015
DOI: 10.3233/bme-151443
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging to determine the potential motor network connectivity between the involved and non-involved hemispheres in stroke

Abstract: Abstract. Hemiparetic stroke is a common motor network disorder that affects a wide range of functional movements due to cortical and subcortical network lesions in stroke patients. Conventional magnetic resonance imaging (MRI) has been used to examine structural brain damage, but the integrity and connectivity of the whole brain are poorly understood. Hence, advanced neuroimaging with diffusion tensor imaging (DTI) has been developed to better localize fiber architecture and connectivity in the motor network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In humans, severity of aphasia has been linked to disruption of structural hubs in a language network (Gleichgerrcht et al , 2015 b ), apathy and post-stroke depression have been found to be related to reduced local and global efficiency in distributed sub-networks. Structurally, reduced centrality measures in stroke hemispheres ( Lee et al , 2015 ), as well as reduced communicability ( Crofts et al , 2011 ) and a modified backbone structure in contralesional hemispheres have been described. In a different cohort, nodal centrality measures of the inferior parietal lobe and the posterior cingulate gyrus were associated with motor impairment on the FM scale and immediate recall, respectively ( Zhang et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, severity of aphasia has been linked to disruption of structural hubs in a language network (Gleichgerrcht et al , 2015 b ), apathy and post-stroke depression have been found to be related to reduced local and global efficiency in distributed sub-networks. Structurally, reduced centrality measures in stroke hemispheres ( Lee et al , 2015 ), as well as reduced communicability ( Crofts et al , 2011 ) and a modified backbone structure in contralesional hemispheres have been described. In a different cohort, nodal centrality measures of the inferior parietal lobe and the posterior cingulate gyrus were associated with motor impairment on the FM scale and immediate recall, respectively ( Zhang et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller integration and higher segregation parameters as well as changes in central network hubs as a result of focal brain damage have previously been described in animal studies using high‐resolution tensor imaging and network simulations (Sinke et al, 2018; Straathof et al, 2019). In addition to reduced measures of centrality in stroke hemispheres (Lee et al, 2015), structural network studies have also revealed changes in the contralateral hemisphere, such as reduced communicability (Crofts et al, 2011) and altered backbone structure(van den Heuvel et al, 2012), after stroke.…”
Section: Discussionmentioning
confidence: 99%